Nanyang 1950-65 : Passage to Singaporean art. - Koichi, Yasunaga; Toshiko, Rawanchaikul; Fukuoka Asian Art Museum, Fukuoka (Fukuoka : Fukuoka Asian Art Museum, 2002)
Chen Wen Hsi ; Cheong Soo Pieng ; Choo Keng Kwang ; Chen, Georgette ; Koeh Sia Yong ; Lai Foong Moi ; Lee Kee Boon ; Lim Hak Tai ; Lim Mu Hue ; Lim Yew Kuan ; Liu Kang ; See Cheen Tee ; Tan Tee Chie
Engels
Japans
Nanyang 1950-65 : passage to Singaporean art, FAAM (Fukuoka Asian Art Museum) Fukuoka, 07.11.2002 - 14.01.2003
boek
Keywords: Singapore